(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Several research have been conducted on the potential impact of mental and psychosocial factors in oral disorders. Different bacterial levels were discovered under situations of stress and relaxation, suggesting that stress may lead to dent caries and that relaxing may have an anticaries effect. The correlation between higher occupational stress and poor dental health was also established. In many instances, no cause can be identified for rapid episodes of tissue collapse. Although it has been difficult to establish a causal link, it is commonly believed that stressful life experiences are connected with illness progression. Therefore, it is essential to identify patients who are under stress and to be able to counsel them on the potential impacts of stress on their general and oral health.